Expert-Based Evaluation of Ecosystem Service Provision in Coastal Reed Wetlands Under Different Management Regimes - Karstens, Svenja; Inácio, Miguel; Schernewski, Gerald (Frontiers in Environmental Science, 2019)
A characteristic feature of lagoons and estuaries along the Baltic Sea is the dominance of reed (Phragmites australis) along their coasts. Reed wetlands are ecologically valuable ecosystems, play an important role for nutrient and matter cycling as well as for biodiversity. They provide a broad spectrum of ecosystem services and are utilized by humans already for centuries. We assess the ecosystem service provision of reed wetlands, analyze how this is affected by different management scenarios and how the results of an expert based ecosystem service assessment can be used in practice. Because of strong internal gradients and interactions with the surrounding, coastal reed belts show a higher ecosystem service provision compared to homogeneous inland reed. The three different coastal management scenarios are 1) winter harvest of reed, 2) summer harvest of reed and 3) grazing by livestock. According to the views of 18 involved experts from Lithuania, Poland and Germany, winter harvest is regarded as the scenario with the lowest conflict potential between nature protection and reed utilization. Experts expect no changes or even slight increases for regulating and cultural services. However, experts see the need to establish a sustainable and regionally anchored winter harvest concept. Summer harvest and grazing entail the risk to change the ecosystem structure and could lead to a shift in vegetation pattern towards short saltmarsh grassland. Experts expect a slight decrease in regulating services. Especially erosion control, biodiversity or nutrient sequestration are rated controversially. To our experience, these expert-based ecosystem service assessments can support policy implementation (e.g. NATURA 2000, European Water Framework Directive or Marine Strategy Framework Directive). It can serve as a tool that allows stakeholders to visualize trade-offs, analyze patterns and processes at regional scales and hence facilitate decision-making.